What is a True Gamer? The Male Gamer Stereotype and the Marginalization of Women in Video Game Culture. - Paaßen, Benjamin; Morgenroth, Thekla; Stratemeyer, Michelle (Sex Roles, 2017)
Women and men play video games in approximately equal numbers. Despite this similarity, video gaming is still strongly associated with men. A common justification for this stereotype is that, although women might play games, they should not be considered 'true' or 'hard-core' gamers because they play more casually and less skillfully compared to their male counterparts. In this contribution, we review the existing literature on gender and gaming to investigate the male gamer stereotype in terms of its accuracy, persistence, effects, and future perspective. We conclude that the stereotype varies in accuracy depending on the definition of 'gamer.' We further argue that the persistence of this stereotype can be explained by the fact that almost all professional and highly visible figures in gaming culture are male. On the other hand, female players who achieve a moderate level of competence are rendered invisible or are actively marginalized. We argue that the effects of the male gamer stereotype can be harmful to women, precluding them from the positive outcomes of video game play such as enhanced access to fields of science, technology, and engineering.